Penataklasanaan Fisioterapi Pada Kasus Tennis Elbow Sinistra dengan Modalitas Transcutaneous Electrical Nerve Stimulation (TENS) dan Hold Relax Exercise di RSUD Ciereng Subang - Anisa Srimulyani; Ika Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tennis Elbow is the formation of abnormal tissue in the wrist extensor muscles which occurs due to inflammation due to excessive contraction. To determine the implementation of Physiotherapy in reducing pain, increasing muscle strength, increasing the Scope of Joint Movement and increasing functional ability and preventing contractures in Tennis Elbow Sinistra cases using Transcutaneous Electrical Nerve Stimulation (TENS) and Hold Relax Exercise modalities. After 6 treatments using VAS, it showed a decrease in movement pain from T1 with a value of 6 to T6 with a value of 3, a decrease in tender pain from T1 with a value of 5 to T6 with a value of 3, while for silent pain T1 to T6 a value of 0. There was an increase in strength. muscles using MMT, namely elbow extension muscle T1 worth 4 to T6 worth 5, elbow flexion muscle T1 worth 3 to T6 worth 5, supination muscle T1 worth 3 to T6 5, pronation muscle T1 worth 3 to T6 worth 5, wrist extension muscle T1 value 4 becomes T6 value 5, while the wrist, radial and ulnar flexion muscles are normal, namely T1 value 5 and T6 value 5. There is an increase in the range of motion of the joints by measuring using a Goneometer, namely in the elbow joint in the sagittal plane T1: 00-00-1450 becomes T6 : 00-00-1500, in the rotation plane T1 : 900-00-700 becomes T6 : 900-00-800, and in the sagittal plane wrist joint T1 : 400-00-500 becomes T6 : 500-00-600, while in The frontal plane is normal, namely T1: 200-00-300 becomes 200-00-300. Transcutaneous Electrical Nerve Stimulation (TENS) can help reduce pain and reduce muscle tension, Hold Relax Exercise can increase muscle strength, reduce stiffness and increase joint range of motion and can help improve functional ability.